Efficacy Of Clarithromycin Versus Oral Steroids In Reducing The Grading Of Nasal Polyps In Pre-Operative Patients Of Functional Endoscopic Sinus Surgery - Javaid, Amna; Chaudhry, Sadia; Masood, Sundas; Bushra, Adia; Sahar, Saba; Umara, Ansa (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the use of oral steroids and clarithromycin in the reduction of Nasal polyp score in pre-operative patients of FESS. Methods: After the ethical approval from the institutional review board, this comparative study was conducted at the Department of Otorhinolaryngology, Head and Neck Surgery, Rawalpindi Teaching Hospital, Rawalpindi Medical University, Rawalpindi from December 2023 to May 2024. Through non-probability consecutive sampling, 60 patients aged between 18-60 years, with Bilateral Nasal polyps and clinically Grade 4, were included in the study. Results: In terms of endoscopic scores, before treatment (Table 2), Group A had a mean score of 3.1 ± 0.6, while Group B had a higher baseline score of 3.6 ± 0.7, with a statistically significant difference between the two groups (p = 0.009). After treatment, the mean endoscopic score in Group A decreased to 2.3 ± 0.70, while in Group B, it decreased more substantially to 1.5 ± 0.56. This difference in post-treatment scores was highly significant (p < 0.0001) (Figure 1). The mean reduction in the endoscopic score was 0.8 ± 0.40 in Group A and 2.03 ± 0.9 in Group B, indicating a significantly greater decrease in Group B (p < 0.0001) Conclusion: Clarithromycin has more anti-polyp effect in terms of size reduction than oral steroids, which provides a strong recommendation towards the management of FESS patients through pre-operative use of the drug.